The complete chloroplast genome sequence of Begonia gulongshanesis (Begoniaceæ). Issue 1 (2nd January 2022) - Guan, Shikai; Song, Qian; Zhou, Jinye; Liu, Yun; Yan, Haixia; Tao, Dayan; Luo, Shuming
Abstract: Begonia L. (Begoniaceae) is the sixth largest genus in the world which consists of more than 2, 039 species. Many species of Begonia have highly ornamental leaves and flowers, so they are mainly used for ornamental purposes, and some species can also be used as medicines or vegetables. Begonia gulongshanensis is a newly discovered species in 2018 which occurs exclusively in Jingxi county in Southern China, however, there are few studies on the molecular biology and phylogeny of this species currently. Therefore, we report its complete chloroplast genome sequence for the first time, hoping to provide a foundation for its future phylogenetic analysis. The chloroplast genome of B. gulongshanensis was 169, 153 bp in size, which contained a large single-copy region of 75, 998 bp, a small single-copy region of 18, 063 bp, and two inverted repeat regions of the same 37, 546 bp. The total GC content was 35.51%. The genome encodes 42 transfer RNA genes, 8 ribosomal RNA genes and 90 protein-coding genes. The phylogenetic analysis indicated that the genetic relationship between B. gulongshanensis and the other three begonias was very close, but there was still certain distance.